Impact of environmental factors on the ammonia-oxidizing and denitrifying microbial community and functional genes along soil profiles from different ecologically degraded areas in the Siding mine. (15th January 2023) - Tang, Shuting; Rao, Yin; Huang, Shulian; Xu, Yue; Zeng, Kaiyue; Liang, Xin; Ling, Qiujie; Liu, Kehui; Ma, Jiangming; Yu, Fangming; Li, Yi
Abstract: Ammonia oxidizers (ammonia-oxidizing bacteria (AOB amoA ) and ammonia-oxidizing archaea (AOA amoA )) and denitrifiers (encoded by nirS, nirK and nosZ ) in the soil nitrogen cycle exist in a variety of natural ecosystems. However, little is known about the contribution of these five N-related functional genes to nitrification and denitrification in the soil profile in severely ecologically degraded areas. Therefore, in the present study, the abundance, diversity and community composition of AOA, AOB, nirS, nirK and nosZ were investigated in the soil profiles of different ecologically degraded areas in the Siding mine. The results indicated that, at the phylum level, the dominant archaea were Crenarchaeota and Thaumarchaeota and the dominant bacteria were Proteobacteria. Heavy metal contents had a great impact on AOA amoA, nirS and nirK gene abundances. AOA amoA contributed more during the ammonia oxidation process and was better adapted for survival in heavy metal-contaminated environments. In addition to heavy metals, the soil organic matter (SOM) content and C/N ratio had strong effects on the AOA and AOB community diversity and structure. In addition, variations in the net ammonification and nitrification rates were proportional to AOA amoA abundance along the soil profile. The soil C/N ratio, soil available phosphorus content and soil moisture influenced the denitrification process. Both soil available phosphorus and moisture were more strongly related to nosZ than to nirS and nirK . In addition, nosZ presented a higher correlation with the nosZ / (nirS + nirK ) ratio. Moreover, nosZ /( nirS + nirK ) was the key functional gene group that drove the major processes for NH4 + -N and NO3 − -N transformation. This study demonstrated the role and importance of soil property impacts on N-related microbes in the soil profile and provided a better understanding of the role and importance of N-related functional genes and their contribution to soil nitrification and denitrification processes in highly degraded areas in the Siding mine. Highlights: AOA amoA contributed more during the ammonia oxidation process. Variations in the net ammonification rate are proportional to AOA amoA gene abundances. Heavy metal contents had a great impact on AOA amoA, nirS and nirK gene abundances. The soil C/N ratio more strongly altered the nosZ gene than the nirS and nirK genes. NosZ /( nirS + nirK ) was a key group promoting the conversion of NH4 + -N and NO3 − -N.